General Concept of Public Policy Implementation - Athaya Yustia Shafa; Lelina Dewi Sahita; Mahardika Putri Laksono; Rima Althea Rianda; Jan Alizea Sybelle (Proceeding International Conference Restructuring and Transforming Law, 2022)
Public policy implementation is the implementation or application of a public policy through programs, activities, actions, or actions in a mechanism that is bound to a certain system. The purpose of writing this article is to discuss the general concept of implementing public policy. The preparation of this article was carried out with the main reference sources from various literatures and research relevant to the implementation of public policy, which were complemented by the author's thoughts on the topics presented. The results of the discussion show that the implementation of public policy is influenced by several factors, including aspects of authority, resources, communication, and disposition. The dimensions that can be used to evaluate the implementation of public policies include consistency, transparency, accountability, fairness, effectiveness, and efficiency. Meanwhile, evaluation of policy implementation needs to be carried out comprehensively, which includes ex-ante, on-going, and ex-post evaluations of theimplementation of public policies. In making innovations and breakthroughs in services to the public, discretion can be exercised in the implementation of public policies as long as they do not conflict with applicable norms and regulations.